The experience of applying vagus nerve stimulation in treatment of pharmacoresistant epilepsy - A. A. Shatokhin; S. M. Karpov; E. V. Kushnareva; I. A. Peshkova; A. V. Shatokhin; I. A. Vyshlova (Эпилепсия и пароксизмальные состояния)
The article presents a clinical case of adult patient with pharmacoresistant epilepsy lacking focal cerebral morphological changes, who was surgically implanted with a vagus nerve stimulation (VNS) system. The results of 6 months-long treatment were analyzed. In addition, available publications were reviewed to evaluate effectiveness of the VNS system in different patient groups. Current clinical case was featured with significant positive dynamics revealed by regression of epileptic seizures and no recorded epileptiform activity based on electroencephalography during VNS stimulation. In the absence of morphological cerebral focal changes in adult patients, installation of the VNS system is an effective and safe method to control pharmacoresistant epilepsy.